CO-INOCULATION WITH RHIZOBIUM AND BACILLUS SP TO IMPROVE THE PHOSPHORUS AVAILABILITY AND YIELD OF WHEAT ( T riticum aestivum L.) . - N. Akhtar; I. Arshad; M. A. Shakir; M. A. Qureshi; J; Sehrish; L. Ali (Journal of Animal and Plant Sciences, 2013)
Intensive cropping has resulted-in wide spread deficiency of nutrients in most of the soils and situation is becoming more serious because of a increase in the use of high priced chemical fertilizers and their negative influence on the environment. Exploitation of biological intervention mainly phosphate solublizing bacteria (PSB) has attracted great attention, as they have enormous potential in providing soil phosphorus for plant growth, by increasing the availability of accumulated phosphate through solubilization. A field experiment was conducted to investigate the effect of Rhizobium and Bacillus, alone and in combination on the yield parameters of wheat. Uniform dose of N and K (160 and 60 kg ha-1), while two levels of P (57 and 114 kg ha-1) were applied as Urea, SOP and SSP, respectively. Bacillus and Rhizobium were applied as seed coating to wheat (Var. Sehar 2006).Results revealed that number of tillers (370.3 m -2), spike length (13.50 cm), number of grains (46 spike-1), grain yield (6171 kg ha-1), biomass (17.00 t ha-1), grain protein (11.84%) and 1000 grain weight (62 g) were higher in co-inoculation of Rhizobium and Bacillus. It was also recorded that coinoculation of Rhizobium and Bacillus improved the grain yield up to 17.5% as compared to control. In single inoculation Bacillus gave better result and showed an increase of 7.7% in grain yield. Phosphorus uptake by grains (25.29 kg ha-1) was maximized by co-inoculation followed by Bacillus inoculation. Available phosphorus in post harvest sample of soil was recorded (16.27 mg kg-1) which was significantly higher than all other treatments. Results clearly demonstrated that co-inoculation of Rhizobium and Bacillus sp enhanced the availability of phosphorus and exert positive effect on the growth and yield of crop.
Keywords: Available phosphorus; Bacillus; Co-inoculation; Rhizobium; Wheat